2014
DOI: 10.1111/ahe.12124
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Studies on the Harderian Gland in the Ostrich (Struthio camelus domesticus) on the Embryonic and Post-natal Period

Abstract: The present investigation was performed on 50 ostriches from 28th day of incubation until the 7th month of life. The morphological (morphometric, histological, histometric and histochemical) studies were conducted. Tissue sections were stained with haematoxylin-eosin, methyl green-pyronin Y, periodic acid-Schiff, alcian blue pH 2.5, aldehyde fuchsin and Hale's dialyzed iron studies. The Harderian gland becomes macroscopically visible on the 28th day of incubation. It is situated in the ventronasal angle of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 26 publications
6
9
0
Order By: Relevance
“…Similar results were obtained by Boydak and Aydin (2009) in domestic geese (Anatidae, Anser anser f. domestica), Canadian ostriches (Frahmand & Mohammadpour, 2015), and African black ostriches (Klećkowska-Nawrot et al, 2015), and also by Kozlu et al (2010) in osprey (Pandionidae, Pandion haliaetus). The average size of lobes of turkeys and chickens, measured by Dimitrov (2011), is larger compared with the common pheasant and the hybrid.…”
Section: Structural Differences Of the Harderian Gland Between Commonsupporting
confidence: 77%
See 3 more Smart Citations
“…Similar results were obtained by Boydak and Aydin (2009) in domestic geese (Anatidae, Anser anser f. domestica), Canadian ostriches (Frahmand & Mohammadpour, 2015), and African black ostriches (Klećkowska-Nawrot et al, 2015), and also by Kozlu et al (2010) in osprey (Pandionidae, Pandion haliaetus). The average size of lobes of turkeys and chickens, measured by Dimitrov (2011), is larger compared with the common pheasant and the hybrid.…”
Section: Structural Differences Of the Harderian Gland Between Commonsupporting
confidence: 77%
“…The histochemical analysis in the present study showed that the HG of both common pheasants and hybrids secreted neutral glycoproteins, as well as acidic sialylated glycoproteins and carboxylated acid mucopolysaccharides. Similar results were obtained with adult domestic geese (Anatidae, Anser anser f. domestica) (Boydak & Aydin, 2009;Liman & Gülmez, 1996), mallard ducks (Anatidae, Anas sterillis) (Dimitrov & Nikiforov, 2005), Canadian ostriches (Frahmand & Mohammadpour, 2015) and African black ostriches (Klećkowska-Nawrot et al, 2015). In native chickens (Phasianidae, Gallus gallus f. domestica), all epithelial cells of the corpus glandulae and duct system reacted positively to neutral mucopolysaccharides and were positive in AB pH 2.5 staining (Mobini, 2012).…”
Section: Structural Differences Of the Harderian Gland Between Commonsupporting
confidence: 68%
See 2 more Smart Citations
“…In the histological examination, the HG in the Capercaillie was defined as a type 1 tubulo-alveolar gland, according to Burns [9], with numerous plasma cells as described in other birds species [4,9,25]. Numerous lymphocytes and plasma cells were found in the peripheral lobular interstitium, interstitium between alveoli as well as the tertiary and secondary ducts of the HG.…”
Section: Acta Biologica Hungarica 67 2016mentioning
confidence: 99%